2006
DOI: 10.1016/j.otohns.2005.03.081
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic Steroid Treatment in Idiopathic Sudden Sensorineural Hearing Loss: A Control Study

Abstract: IT steroid administration after failed intravenous steroids is a safe and effective treatment in sudden sensorineural hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
178
3
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(191 citation statements)
references
References 22 publications
7
178
3
3
Order By: Relevance
“…Despite this variability, 3 of the 4 RCTs evaluating intratympanic steroids as salvage therapy found that IT steroids improved hearing outcomes beyond placebo. Hearing improvement occurred in 53% to 90% of patients [29,30] Table 2. IT steroids are to be started on the 1 st day when patient approaches the doctor. It can be used as a main stay of treatment or as an adjuvant treatment with other modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this variability, 3 of the 4 RCTs evaluating intratympanic steroids as salvage therapy found that IT steroids improved hearing outcomes beyond placebo. Hearing improvement occurred in 53% to 90% of patients [29,30] Table 2. IT steroids are to be started on the 1 st day when patient approaches the doctor. It can be used as a main stay of treatment or as an adjuvant treatment with other modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Xenellis, et al [30] IT methylprednisolone (40 mg/mL) with a 21 gauge needle, four times over 15 days.…”
Section: Discussionmentioning
confidence: 99%
“…Several others studies have supported IT DEX as salvage therapy, while other lack sufficient evidence of success [9,12,17,19,[20][21][22][23] . Among the factors that could influence hearing outcome, time from onset of HL to the baseline visit was found to be statistically significant (p=0.030).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also described the use of intratympanic corticosteroids for the treatment of SHL. 9,[12][13][14][15][16][17][18][19][20][21][23][24][25][26][27] Although its efficacy alone has not been proved definitively, intratympanic corticosteroid therapy for SHL is becoming more widely used. The variability among treatment protocols for SHL also applies to intratympanic corticosteroid therapy.…”
Section: Intratympanic Therapymentioning
confidence: 99%
“…13,15,16 Most studies about intratympanic corticosteroids for treating SHL report having attempted this mode of therapy after systemic corticosteroid therapy has failed. 9,[12][13][14][15][16][17][18][19][20][21][25][26][27] Two studies evaluated the effects of intratympanic corticosteroids as adjuvant therapy to systemic corticosteroids in SHL patients. 23,24 There are several advantages of using intratympanic corticosteroids (see Frame I).…”
Section: Intratympanic Therapymentioning
confidence: 99%